Եղիա Տեմիրճիպաշյանը՝ հրապարակագիր - Դեմիրճյան, Պետրոս (ՀՀ ԳԱԱ)
XIX դարի 80-ական թվականների բուռն ու բեղուն տարիներին ամենից առաջ ի հայտ եկավ երիտասարդ Եղիա Տեմիրճիպաշյանի հրապարակագրական ձիրքը: Իր հրատարակած պարբերականներում նա անդրադառնում է հայոց ազգային, հասարակական, կրոնական, գրական-մշակութային, կրթական-մանկավարժական եւ բազմազան այլ հարցերի ու խնդիրների: Դրանք արդյունք էին ոչ միայն Եղիայի անհատական ըմբռնումների ու նախասիրությունների, այլեւ նախ եւ առաջ ժամանակի պահանջի, ավելի ընդհանուր՝ մարդկային մտքի առաջընթացով պայմանավորված՝ կյանքի արդիական փոփոխությունների թելադրանքի, հնի ու նորի, դարն ապրածի ու ապագային միտված ծիլերի պայքարի: Публицистический талант молодого Е. Темирчипашяна впервые проявился в 80-е годы XIX века. Он обращался к национальным, общественным, религиозным, литературно-культурным, учебно-педагогическим и другим вопросам, связанным с армянской реальностью. Они явились результатом не только индивидуальных предпочтений Е. Темирчипашяна, но и, прежде всего, были продиктованы временем и обусловлены прогрессом человеческой мысли, диктатом современных перемен в жизни, борьбой старого и нового. Егия Темирчипашян выступал убежденным сторонником и поборником благотворных изменений в национальной и человеческой жизни. Борясь за прогресс, он сталкивался с непониманием или нетерпимостью, неприятием нового. Расширение представлений науки о человеке, природе, обществе и Вселенной имело не только положительные, но и отрицательные последствия, что вызывало у него глубокую обеспокоенность будущим человечества в целом и армянского народа в частности. In the tumultuous and fertile years of 80s of the XIX century, the publishing talent of young Yeghia Temirchypashyan first emerged. In his published periodicals, he refers to Armenian national, social, religious, literary-cultural, educational-pedagogical and various other issues and problems. They were the result not only of Yeghia’s individual understandings and preferences, but also, first of all, the demand of the time, more generally, the dictate of modern changes in life, the struggle of the old and the new, the old and the future-oriented sprouts due to the progress of human thought, Yeghia Te- mirchypashyan acted as a convinced supporter of nature, national and human welfare. Fighting for progress, he found, however, that it was moving very slowly. Too often it runs into a wall of incomprehension or intolerance. The expansion of scientific ideas about human being, nature, society and the universe brings with it not only positive but also negative realities, sometimes with irreversible consequences, which deeply worried many people, including himself, Yeghia. But the problem is not only among the Arme- nians or the nation. Ye. Temirchypashyan gradually broadens and deepens the range of questions, including the problem of the current state and future, destiny of man and humanity in general. Finally, to the most important questions "Where will we go?" Where will Armenia go? Where would humanity go?, the answer, in fact, was still uncertain: "I don't know". There are only vague premonitions of the future, with accents of anxiety and despair, from which, as Yeghia confesses, "My soul grieves for death...".
Keywords: Բանասիրություն